1996
DOI: 10.1074/jbc.271.19.11317
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Attenuates Vascular Smooth Muscle Cell Activation by Interferon-γ

Abstract: Atherogenesis involves cellular immune responses and altered vascular smooth muscle cell (SMC) function. Cytokines such as interleukin (IL)-1 alpha and interferon-gamma (IFN-gamma) may contribute to this process by activating SMC. To determine whether the anti-atherogenic mediator, nitric oxide (.NO), can modulate cytokine-induced SMC activation, we investigated the effects of various .NO-generating compounds on the expression of intercellular and vascular cell adhesion molecules (ICAM-1 and VCAM-1). Induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(69 citation statements)
references
References 43 publications
5
62
2
Order By: Relevance
“…In contrast, this report and previously published data (89) suggest that the G-14 variants have a reduced affinity for ISGF3␥ but bind IRF1 and IRF2 with high affinity. The latter ICS elements are not IFN responsive and are capable of constitutively activating transcription (14,26,48,74).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, this report and previously published data (89) suggest that the G-14 variants have a reduced affinity for ISGF3␥ but bind IRF1 and IRF2 with high affinity. The latter ICS elements are not IFN responsive and are capable of constitutively activating transcription (14,26,48,74).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the histone H4 genes, the only known requirement for EBNA1 in EBV-infected cells involves the binding of EBNA1 to the EBV latent origin of replication (oriP) during S phase of the cell cycle, thereby allowing the EBV episome to be replicated coordinately with cellular genomic DNA (98,99). Thus, EBNA1 might be produced in a cell cycle-regulated manner, with peak production occurring [40], histone H4 [88], PRDI [89], IFN-␣1 [14], VCAM1 [74], TAP1 [48], H2K b IRS [30], factor B [96], 2Ј-5Ј OAS [66], and 6-16 [59]). The nucleotide at position 14, which appears to correlate with IFN-␣/␤ inducibility, is boxed.…”
Section: Figmentioning
confidence: 99%
“…This finding is of particular interest considering the complex role exerted by nitric oxide in the homeostasis of endothelial cells [18,19] and in the regulation of leukocyte-endothelium interaction [20][21][22]. In this regard, it is well known that an acute decrease in NO production by the vascular endothelium up-regulates endothelial cell adhesion molecule expression (i.e., P-selectin and ICAM-1), thus enhancing leukocyte-endothelial interaction [12,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Others have found that treatment with NO donors, such as SNAP, suppressed the NF-B DNA-binding activation in human EC (75) and vascular smooth muscle cells (76). In the current study, SNAP pretreatment alone was not sufficient to inhibit NF-B DNA-binding activity in TNF-␣-activated porcine ECs.…”
Section: Discussionmentioning
confidence: 53%